FIQH CAGAR BUDAYA: REKONSTRUKSI FIQH ISLAM DALAM BINGKAI PERADABAN NUSANTARA - Misno (JURNAL ALAMIAH, 2021)
Indonesia is a large nation that has an abundance of historical cultural heritage. Efforts to preserve it have been made by protecting the cultural heritage. However, damage to cultural heritage objects continues to occur. One reason is because of the religious element. Worrying about making people commit acts of shirk is one of the reasons. Damage to cultural heritage objects occurs in various Islamic countries for the same reason, Iraq, Syria, Afghanistan and Saudi Arabia are countries with high levels of cultural heritage damage. How does Islam view the protection of cultural heritage? Fiqh as an element of Islamic law has a dynamic and flexible nature, one of its basic characteristics is that it is friendly to tradition and culture. The concept of Nusantara fiqh provides a solution in the destruction of cultural heritage objects. The legal basis for protecting cultural heritage is; adat and 'urf of Muslims in Indonesia, benefit, collective ijtihad and analogy-deductive. Finally, cultural heritage fiqh is an element of Islamic law that protects cultural heritage objects.